Self-immobilised bacterial consortium culture as ready-to-use seed for crude oil bioremediation under various saline conditions and seawater - W., Kok Kee; Hazaimeh, Mohammad; Mutalib, S. A.; Abdullah, P. S.; Surif, S. (Springer Berlin Heidelberg, 2014)
Biodegradation of crude oil hydrocarbon by microorganisms in seawater is generally slow because of the harsh environmental condition due to high salinity. The aim of this study was to compare sawdust (SD) and oil palm empty fruit bunch wastes as suitable carrier material to immobilise hydrocarbon-degrading bacterial consortium culture to accelerate and improve crude oil degradation in seawater. The consortium culture was found able to tolerate salinity up to 3 %, where the degradation of crude oil was not inhibited (p > 0.05). In artificial seawater, suspension of bacterial consortium culture was able to degrade 83.3 ± 3.00 % of crude oil within 8 weeks, which indicated the possibility of using consortium culture in seawater. When tested in seawater, suspension of consortium culture managed to degrade 47.7 ± 1.53 % of crude oil in 8 weeks. In order to improve the performance of consortium culture, immobilisation of consortium culture onto SD and oil palm empty fruit bunch was successfully undertaken when formation of biofilm layers was observed under scanning electron microscope. Immobilising consortium culture onto oil palm empty fruit bunch and SD was shown to increase crude oil biodegradation to 68.7 ± 4.04 and 62.3 ± 5.51 % in 8 weeks, respectively. This study demonstrated immobilisation of consortium culture onto SD and oil palm empty fruit bunch can be utilised as ready-to-use seeds to improve and accelerate crude oil biodegradation in seawater.